Deformation history of the Qianlishan Complex, Khondalite Belt, North China: Structures, ages and tectonic implications. (December 2020) - Yin, Changqing; Qiao, Hengzhong; Lin, Shoufa; Li, Changcheng; Zhang, Jian; Qian, Jiahui; Wu, Shangjing
Abstract: The Qianlishan Complex is a multiply deformed granulite terrane of the Khondalite Belt that represents a Paleoproterozoic continent-continent collisional orogen in the Western Block of the North China Craton. Two major stages of deformation (D1 and D2 ) were identified in the Qianlishan Complex. D1 mainly produced NWW-trending overturned to recumbent intrafolial isoclinal folds F1, sub-horizontal penetrative foliations S1, NNE-SSW mineral lineations L1 associated with top-to-the-SSW thrust shear, reflecting crustal thickening due to the NNE-SSW compression. D1 was developed with the prograde (M1 ) and peak (M2 ) granulite-facies metamorphism. D2 successively superposed the D1 structures and was characterized by NWW-SEE-trending doubly plunging open to tight upright folds F2 and minor sub-vertical axial planar foliations/cleavages S2 . D2 was accompanied by post-peak near-isothermal decompression (M3 ), probably related to exhumation following the crustal thickening. SIMS U–Pb zircon ages of deformation-related leucocratic dykes demonstrate that D1 broadly occurred at 1976–1936 Ma and D2 subsequently happened at 1936–1854 Ma. These results indicate that the Khondalite Belt underwent long-term ( 100 Myr) polyphase deformation and high-grade metamorphism associated with magmatism. Timing constraints and kinematic compatibility suggest that the deformation sequence resulted from the NNE-SSW collision between the Yinshan and Ordos Blocks to form the Western Block at 1.95 Ga. Graphical abstract: fx1